Argumentation-Based Risk Management - Severo, Fabrício S.; Pozzebon, Ruan C. B.; Fontoura, Lisandra M.; Silva, Luís A. L. (Anais do Simpósio Brasileiro de Sistemas de Informação (SBSI), 2013)
Collaborative risk management is a fundamental task in project management. This paper discusses a new collaborative approach to risk management which is grounded on the integration of dialogue games and argument schemes from argumentation research. In particular, we propose a new dialogue game to organize risk discussions, and the exploitation of typical argument schemes for risk management on the collection of more complete arguments. A new collaborative Risk Discussion System is discussed and evaluated, where its environment is capable of structuring and recording risk discussions in a project management memory.